Pengaruh Store Atmosphere Terhadap Niat Beli Ulang Konsumen di Outlet Richeese Factory Gatot Subroto Kota Bandung - Safra Hanafi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Fast food restaurants remain popular and in demand among the Indonesian people because food and beverages are basic needs. Therefore, it is important for restaurant owners to create a store atmosphere through various elements that can influence consumers emotions and perceptions, encouraging them to make purchases. Richeese Factory, as one of the fast food restaurants, continues to follow market demand by rebranding its store atmosphere. This change includes redesigning the building to be more Instagramable with a modern industrial concept. This study aims to understand consumers perceptions of store atmosphere, consumers repurchase intentions and the relationship between these two variables. A quantitative research method with a descriptive approach was used, employing non-probability sampling and a semantic differential scale. The results show that respondents agreed with the variables of interior, exterior, store layout, interior display and repurchase intention. Overall, all aspects of store atmosphere and repurchase intention were positively received by respondents. Thus, it can be concluded that store atmosphere significantly influences consumers repurchase intentions at Richeese Factory Gatot Subroto Bandung.